Immunopathogenecity of Different Types of Toxoplasma Gondii - Subekti, Didik T; Arrasyid, Nurfida K (Indonesian Animal Sciences Society, 2006)
Toxoplasmosis is a zoonotic disease caused by Toxoplasma gondii . The disease was widely found in high prevalence around the world . Seroprevalence of human toxoplasmosis in Indonesia was 43 - 88% while toxoplasmosis in animals was reported 6 - 70%. In the past, clinically manifestation of toxoplasmosis only occurred in individu which has immunodeficient or immunosupression . Recently, more evident showed that individu which has immunocompetent was also able to develop clinical signs when infected by pathogenic T gondii (type I of T gondii) . In fact, the pathogenicity of T. gondii depends on the type or closet which originated from their clonal population . Each type has different implication on clinical immunopatho genesis . In this paper, the differences of biological character, immunopathogenicity and their clinical implication of T gondii clonal population structure are reviewed. Key words : Toxoplasma gondii, clonal population, immunopathogenecity